Local Government Strategies in Developing Tourism Destinations in Sumedang Regency - Deden Haria Garmana; Ade Opik Rohmanudin (Department of Public Administration, 2026)
This study aims to investigate strategies for developing tourism in Sumedang Regency carried out by the Office of Culture, Tourism, Youth, and Sports Affairs. This research was conducted using qualitative descriptive methods in a naturalistic setting. Data collection techniques were carried out through observation, interviews, and documentation. Four subjects in this study were selected through purposive sampling. Meanwhile, the data analysis employed was Miles and Huberman’s model, which consisted of the following steps: data reduction, data presentation, and verification. The findings of this research indicated that the strategy for developing tourism in Sumedang had been implemented. However, the implementation was not optimal. It can be seen that tourism marketing was still not optimal due to: (1) the diversity of people's desires for tourism. Thus, there were difficulties in determining the target market, and (2) the accessibility and quality of the infrastructure. Some tourism destinations did not meet the standards in their infrastructure. Researchers recommended that a data inventory related to tourism in Sumedang was needed, such as places that have the potential to be attractive tourist destinations, marketing strategies for tourism which fit with their target market, as well as urgent infrastructure improvements to tourism spots in Sumedang Regency because infrastructure is the main factor for bringing in both local and foreign tourists.